Problems of Understanding and Embodiment in Parmenides B 16/D51 - Cherubin, Rose (Peitho. Examina Antiqua, 2024)
Parmenides B 16/D51 presents an account of human cognition and understanding. It is usually taken to form part of the account of the untrustworthy opinions of mortals. Regardless of its proper location within the poem, it invokes difference, movement, and multiplicity — features that the goddess describes as fundamental to mortals’ opinions and as incompatible with what one must say and conceive on the road of inquiry that she recommends. The tale of the journey and both parts of the goddess’s speech use negation, invoke difference and change and multiplicity, and in general conform in many ways to the conceptual framework the goddess attributes to mortals in B8.53-61/D8.58-66 and B9/D13. Does this reflect confidence in the Light-Night conception as a starting-point for an adequate account of what-is? Or does it produce a paradox, wherein the Light-Night conception undermines itself but we would have to use it in order to deny its adequacy? In sum, what kind of a claim about human understanding might the passage represent? What could B16/D51 say about the epistemological status of its own claims, and about the epistemological status of each part of the poem? Why does the passage mention humans (anthrōpoi) specifically, as opposed to all beings that have awareness? These questions will be the focus of this essay.